CLINICO-TRICHOSCOPIC EVALUATION OF HIRSUTISM TREATED WITH INTENSE PULSED LIGHT IN A TERTIARY CARE HOSPITAL IN EASTERN INDIA - CHINJITHA, DAVIS T; Joyeeta, CHOWDHURY; Suchibrata, Das; Arun, Achar; Alok, Roy K (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study is to determine the effectiveness of Intense Pulsed Light in treating hirsutism after three sittings, as evaluated through clinical and trichoscopic assessments, in patients attending a tertiary care hospital in Eastern India. Methods: This was a Descriptive Longitudinal study conducted at the Dermatology Outpatient Department (OPD), Government Medical College, Kolkata, from March 2019 to February 2020. The study included 40 cases of Dermatology OPD attendees who complained of hirsutism. Trichoscopy was used to evaluate treatment response. Data were analyzed using Medcalc. Results: Seventy percent had functional while 30% had organic hirsutism; 65% patients had PCOD and 27.5% had idiopathic hirsutism. All the patients had significant improvement with intense pulsed light with regard to terminal-vellus hair ratio and Terminal hair density observed with trichoscopy irrespective of their medical treatment. The mean modified visual analog score was 6.75±1.1209. According to the modified visual analog score, 57.5% had good reduction while the rest had a moderate reduction. Conclusions: The majority had functional hirsutism. Polycystic ovarian disease and idiopathic hirsutism are the most common causes of hirsutism. Intense pulsed light is an effective and safe method of hair removal, regardless of medical treatment, and trichoscopy can be used to evaluate treatment response.